The consequences of judicial obligations as a politics of transition in post-war Serbia, Bosnia and Herzegovina, and Croatia - Veljanovska Michelle (Temida, 2012)
This paper explores the idea of victimhood from the individual to societal level within the context of transitional justice and reconciliation. The idea of justice and truth has gained considerable prevalence within post-war states in the Balkan region. The reform of the state has required the regeneration of society based on particular legal interpretations of the political violence. As a result, an era of judicial obligations has come to frame how society regenerates, reforms and rehabilitates. Therefore the paper discusses the consequences of wartime victimization in terms of local responses to how ‘the past is processed’ through Transitional Justice institutions like the International Criminal Tribunal of Yugoslavia (ICTY), and associated ad-hoc mechanisms, like outreach programs. The establishment of such judicial processes have set off particular questions like can society be seen as victim? How is society victim? Using a socio-political approach, such questions are problematised through a political defeat paradigm to reveal a particular political anxiety that underwrites the new societies and their politics. This is where the idea of “state anxiety” and “political defeat” are used to discuss what has locally formed out of such politics of transition.